Ten Twinkly Stars - Julian, Russell 1975- (Wilton, CT Tiger Tales, 2015)
EARLY LEARNING: NUMBERS & COUNTING. Join the adorable animals as they snuggle and snooze beneath the twinkling stars in this enchanting book. Young readers will delight in the colorful, tactile pages as they watch the die-cut stars decrease from 10 to 1 with each turn of the page. Ages 0+
"Colorful countdown fun!" -- cover.
Keywords: Stars; Juvenile fiction; Animals -- Juvenile fiction; Counting -- Juvenile fiction; Fiction; Novels